Optimalisasi Kualitas Butir Soal melalui Pelatihan Penyusunan Indikator dengan Uji Validitas dan Reliabilitas - Handoko, Handoko; Rohman, Fatkhur; Farha, Syahla Athiya; Putri, Hana Salsabila; Sucitra, Diah Ayu (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
The quality of learning evaluation instruments is often suboptimal due to teachers' limitations in developing indicators, validity, and reliability of questions. This community service activity aims to improve teachers' competence through participatory training that includes indicator development, question writing practice, validity and reliability testing, question bank development, and guide module creation. The results show an increase in teachers' understanding and skills in producing questions that are appropriate, valid, and reliable. The outputs in the form of a question bank and guidance module are useful as practical references in learning evaluation, in line with previous studies that emphasize the importance of strengthening teachers' assessment competencies.